2018
DOI: 10.5005/jp-journals-10024-2345
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Selective Serotonin Reuptake Inhibitors in Osseointegration of Dental Implants: A 5-year Retrospective Study

Abstract: Failure rates of dental implants are significantly increased in patients taking SSRIs due to depression. Careful case analysis and history of depression may minimize the failure rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…Various animal and in vitro studies have linked SSRI drugs to bone metabolism. In fact, in the studies analyzed, albeit few in the literature, most have found a higher percentage of implant failure compared to control groups [7][8][9][10][11]. Osteoclasts are stimulated to proliferate due to the presence of serotonin, whereas osteoblasts are inhibited to differentiate themselves from hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Various animal and in vitro studies have linked SSRI drugs to bone metabolism. In fact, in the studies analyzed, albeit few in the literature, most have found a higher percentage of implant failure compared to control groups [7][8][9][10][11]. Osteoclasts are stimulated to proliferate due to the presence of serotonin, whereas osteoblasts are inhibited to differentiate themselves from hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another paper published in 2018 explored the effect of SSRIs on 352 patients with 680 dental implants (Deepa et al, 2018). The authors found a certain difference between assumers and not assumers in terms of implant failure, even though the effect of important risk factors was not adequately controlled between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…One study published in 2018 on a cohort composed of 631 patients (36 using SSRIs) with a total of 2055 implants failed to find a significant correlation between SSRIs assumption and implant failure, without any analysis of the correlation between SSRIs and peri‐implantitis (Altay et al, 2018). Another paper published in 2018 explored the effect of SSRIs on 352 patients with 680 dental implants (Deepa et al, 2018). The authors found a certain difference between assumers and not assumers in terms of implant failure, even though the effect of important risk factors was not adequately controlled between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…This allows observing that with the current increased life expectancy, patients are also looking for greater social interaction, revealing aspects of personal satisfaction with their appearance, which have a positive influence on quality of life. [6,7] Referring to this age group (41-60 years), strategic causes were the main reasons for exodontia (160) for protocol implants, followed by prosthetic and associated causes, both with 86 of the 493 cases. The retrospective analysis showed that both sexes were included in this opinion, especially the female sex (64.1%).…”
Section: Discussionmentioning
confidence: 99%